La prévention des problèmes de comportement à l’adolescence : le Adolescent Transition Program - Poulin, François; Dishion, Thomas; Kavanagh, Kate; Kiesner, Jeff (Criminologie, 1998)
The Adolescent Transition Program (ATP) is a multi-component preventive intervention designed to reduce escalation in problem behaviors among high-risk young adolescents. A previous evaluation of this program showed that aggregating high-risk youths for intervention purposes led to an escalation in delinquency and smoking. The results of this study also suggested that an intervention targeting parenting practices was more beneficial. These findings led to the development of a new intervention program aimed at the modification of parenting practices. This school-based program proposes a multiple gating approach to parent intervention with each level of intervention building on the previous one to reduce the overall prevalence of risk. A pilot study designed to evaluate the implementation of this intervention program suggested that schools seem to be an appropriate setting for reaching parents of high-risk adolescents and delivering intervention services.